2022
DOI: 10.1186/s12917-022-03334-0
|View full text |Cite
|
Sign up to set email alerts
|

Serological investigation of Gyrovirus homsa1 infections in chickens in China

Abstract: Background Gyrovirus homsa1 (GyH1) (also known as Gyrovirus 3, GyV3) is a non-enveloped, small, single-stranded DNA virus, which was first identified in children with acute diarrhea, and was subsequently detected in marketed chickens, broilers with transmissible viral proventriculitis (TVP), and mammals. GyH1 is a pathogenic virus in chickens, causing aplastic anemia, immunosuppression, and multisystem damage. However, the seroepidemiology of GyH1 infection in chickens remains unclear. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Importantly, GyH1 co–infection with CAV leads to higher mortality and more widespread lymphocyte apoptosis [ 19 ], which increases the risk posed and makes prevention and control more difficult. Specifically, epidemiology investigation suggests that GyH1 is widespread in China, which is consistent with our findings [ 17 , 18 , 20 ]. Thus, an accurate diagnosis of GyH1 is particularly important.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, GyH1 co–infection with CAV leads to higher mortality and more widespread lymphocyte apoptosis [ 19 ], which increases the risk posed and makes prevention and control more difficult. Specifically, epidemiology investigation suggests that GyH1 is widespread in China, which is consistent with our findings [ 17 , 18 , 20 ]. Thus, an accurate diagnosis of GyH1 is particularly important.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the highest positive rate of GyH1 occurred in 2019, which may be because after the pathogenicity of GyH1 attracted widespread attention, breeders stepped up preventive measures to reduce the infection rate [ 14 ]. Furthermore, the molecular epidemiological and seroepidemiological results further confirm our conclusions [ 18 , 20 ].…”
Section: Discussionsupporting
confidence: 87%
“…GyH1 infection in chickens causes aplastic anemia, immunosuppression, and TVP [ 17 ]. Sero-epidemiological investigation indicates that GyH1 infection is widespread in chicken farms in China [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…N-terminal pro-B-type natriuretic peptide (NT-proBNP), a member of the diuretic natriuretic peptide family secreted by the heart, regulates the homeostasis of blood pressure and blood volume and has a diuretic effect. NT-proBNP correlates with the occurrence of AKI and may be of great value as a biomarker for the early prediction of AKI ( Zhang et al, 2022 ). HE4, a novel tumor marker, has good predictive value for the progression of ovarian cancer ( DeBoer et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%